MUTU SENSORI KOPI LUWAK ASAL DATARAN TINGGI GAYO - Murna Muzaifa; Yusya Abubakar; Febriani Febriani; Amhar Abubakar; Dian Hasni (AGROINTEK, 2021)
Indonesia is rich in specialty coffee. Some of the specialty coffees from Indonesia are Lintong coffee, Mandailing coffee, Gayo coffee, Toraja coffee and others. Luwak coffee with unique processing is categorized as specialty coffee. Luwak coffee is known as one of the special and most expensive coffees in the world. The Gayo Highlands, as one of the best and largest arabica coffee producing areas in Indonesia, also produces civet coffee. It is suspected that the quality of Gayo arabica civet coffee is also very good. This study aims to analyze the sensory quality of civet coffee from the Gayo Highlands. The results showed that civet coffee from the Gayo Highlands has various sensory. The quality of the cupping score is very good 83.75 (very good) -85.75 (excellent) with the most dominant aromas being nutty, fishy, chocolaty and herby